The association between unemployment status and physical health among veterans and civilians in the United States. (20th October 2016) - Tran, Thanh V.; Canfield, Julie; Chan, Keith
ABSTRACT: This study analyzed data from the 2012 Behavioral Risk Factor Surveillance System to examine the association between unemployment status and physical health among a sample of 170, 924 civilians and 12, 129 veterans (aged 18–50 years). Multivariate regression analysis was used to test the interaction effect between employment status and veteran/civilian status on physical health. Veterans who were unemployed long term (longer than 27 weeks) reported a significantly greater number of days with poor physical health than civilians who experienced long-term unemployment. Timely prevention and intervention efforts to integrate veterans into the workforce could lead to substantially improved physical health outcomes. Public health policies and programs that are funded to assist veterans in securing and maintaining gainful employment can have lasting implications for their overall improved health and physical well-being.